Optimization of triple-junction hydrogenated silicon solar cell nc-Si:H/a-Si:H/a-SiGe:H using step graded Si1‑xGex layer - Nji Raden Poespawati; Rizqy Pratama Rahman; Junivan Sulistianto; Retno Wigajatri Purnamaningsih; Tomy Abuzairi (Institute of Advanced Engineering and Science, 2021)
This paper shows the attempt to increase the performance of triple-junction hydrogenated silicon solar cells with structure nc-Si:H/a-Si:H/a-SiGe:H. The wxAMPS software was used to simulate and optimize the design. In an attempt to increase the performance, an a-SiC:H layer on the p-layer was replaced with an a-Si:H layer and an a-SiGe layer was replaced with a step graded Si1-xGex layer. Then, to achieve the best performing device, we optimized the concentration of germanium and thickness of the step graded Si1-xGex layer. The result shows that the optimum concentration of germanium in the p-i upper layer and i-n lower layer are 0.86 and 0.90, respectively and the optimum thicknesses are 10 nm and 230 nm, respectively. The optimized device performed with an efficiency of 19.08%, adding 3 more percent of efficiency from the original design. Moreover, there is a significant possibility of increasing the efficiency of a triple-junction solar cell by modifying it into a step graded Si1-xGex layer.